Local Government Financial Performance: Good Governance, the Efectiveness Internal Control and Competence - Budiharjo, Roy; Pratomo, Dudi; Hapsari, Dini Wahjoe (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Good governance is an important foundation in creating transparency, accountability, and integrity in organizational management. This study aims to analyze how the principles of good governance, internal control and competence of the financial performance of the Bekasi City local government are moderated by internal control. This study uses a quantitative methodology with a sample of 41 respondents who are financial employees in the Bekasi City government with statistical testing using Smart PLS 3.0. The results of the study found that (1) good governance, internal control and competence have a positive effect on the financial performance of the local government. (2) Good governance contributes to creating transparency and accountability. (3) Internal control in good financial reporting can prevent deviations. In addition, this study also found that the competence of human resources in the financial sector plays an important role in effective budget management. This study provides recommendations that the importance of improving governance, internal control, and human resource competence as a strategic effort to improve the financial performance of the local government.